Deterring hooded crows from re‐nesting on power poles - Guillam E. McIvor; Candy Rowe; Susan D. Healy (Wildlife Society Bulletin, 2012)
Abstract Hooded crows (Corvus cornix) nest on power poles throughout the north of Scotland, and the interruptions to electricity supply caused by the nests cost the electricity provider in excess of (UK) £250,000 annually. In the Orkney Isles, where pole nesting is relatively common, most nests are actively removed before they can cause a fault. However, rebuilding often occurs. Although the electrical company routinely fits Firefly FF‐type diverters (P & R Tech Inc., Beaverton, OR, USA) after nest removals to deter the crows from rebuilding, there has been no field test of the effectiveness of the Fireflies as a deterrent. In our study, carried out in Orkney in the Spring/Summer of 2009 and 2010, Fireflies were fitted at half of the sites from which nests were removed and not fitted at the other half of the sites. We found that crows were equally likely to rebuild at sites fitted with Fireflies as they were to rebuild at sites without Fireflies. However, rebuilding was less likely to occur the later in the season that nests were removed, and nests in the middle phase of construction were the most likely to be rebuilt. Therefore, making an appropriate decision as to when to remove a crow nest seems to be a more effective method for deterring nest rebuilding than is the fitting of Firefly diverters. © 2012 The Wildlife Society.